Mapping the landscape of virtual word of mouth (v-WOM) in the tourism sector: A bibliometric review - Jyoti Jyoti; Jitender Kumar (Tourism)
The increasing significance of virtual word of mouth (v-WOM) in the digital era has the potential to revolutionize consumer decision-making across a wide range of markets such as tourism. The objective is to review the literature on v-WOM published between 2013 and 2023 and the research employs bibliometric analysis to examine 718 documents from the Scopus database. For performance and science mapping analysis, Biblioshiny and VOSviewer were utilized. The growing trend in publication and citation numbers shows that v-WOM is a growing field and the prominent journals involving tourism research are Tourism Management and International Journal of Hospitality Management. Robert Law is a well-known author and China has the greatest number of publications. The conceptual themes of v-WOM literature were formed by the co-occurrence analysis of keywords and bibliographic coupling networks. In order to provide insights for the future, a word cloud analysis of 549 documents published in the previous four years was also carried out.